Gravity Wave Source Spectra Appropriation for Mesosphere Lower Thermosphere Using Meteor Radar Observations and GROGRAT Model Simulations. Issue 19 (24th September 2020) - Pramitha, M.; Kumar, K. Kishore; Ratnam, M. Venkat; Praveen, M.; Rao, S. Vijaya Bhaskara
Abstract: Meteor radar observations of gravity wave momentum fluxes (GWMFs) in the 82–94 km altitude region, which is a part of mesosphere lower thermosphere (MLT), are employed to identify the best fit gravity wave source spectrum using Gravity wave Regional or Global Ray Tracer (GROGRAT) model simulations over a low‐latitude location, Tirupati (13.63°N, 79.4°E). GROGRAT model is used to propagate a spectrum of gravity waves from the troposphere to the lower thermosphere. A total number of five gravity wave source spectra with various permutations and combinations are considered for the model simulations and by comparing the model simulated and radar observed gravity wave fields in the 82–94 km region, a best fit source spectrum is identified. The significance of the present study lies in appropriating the gravity wave source spectrum using meteor radar observations for the first time, which will have implications in improving gravity parameterization schemes in global models. Plain Language Summary: Gravity waves are ubiquitous in the Earth's atmosphere and play a pivotal role in coupling lower and upper atmosphere. Once generated in the lower atmosphere, these waves carry momentum and energy and deposit somewhere in the middle and upper atmosphere. One of the important areas of research in the realms of middle atmospheric dynamics is to identify the source spectra of these waves so that they can be represented reasonably well in the numerical models. In the present communication, five different forms of source spectra with several combinations of parameters are employed to estimate the gravity wave momentum fluxes using a ray tracing model. The simulated gravity wave momentum fluxes in the 82–94 km region are then compared with those estimated from meteor radar located at a low‐latitude station, Tirupati [13.63°N, 79.4°E]. The source spectrum, which simulates the meteor radar observed gravity wave momentum fluxes reasonably well, is identified to be the best fit spectrum. The present results are first of their kind and have implications in representing gravity wave source spectra in numerical models. Key Points: GROGRAT model simulations and meteor radar observations are employed to identify the best fit gravity wave source spectrum for mesosphere lower thermosphere for the first time The gravity wave momentum fluxes measured by meteor radar and simulated by GROGRAT model agree reasonably well at seasonal scales The identified best fit source spectrum is employed to estimate momentum fluxes at the source level